Bron R. Taylor (editor-in-chief), The Encyclopedia of Religion and Nature - Dalton, Anne Marie; Erhard, Nancie (Journal for the Study of Religion, Nature and Culture, 2006)
Bron R. Taylor (editor-in-chief), The Encyclopedia of Religion and Nature (London and New York: Thoemmes Continuum, 2005), I and II, pp. xxlv +1877. Hardback $450, £250, ISBN 1-8437-1138-9.